Impacts and Opportunities at the Climate–Land Use–Energy–Water Interface: An Urgent Call for Dialogue. (1st June 2022) - Jacobs, Kathy; Holway, Jim; Hanak, Ellen; Quay, Ray; Sternlieb, Faith; Udall, Brad
Abstract: Historically, managers of land, energy, and water systems have not recognized the importance of the collective interconnections of these systems. It is simpler to think about these intersections as two‐dimensional rather than multi‐dimensional puzzles. However, in the context of climate change, the multiple intersections between systems need to be examined. Failure to consider those connections can result in under‐appreciated risks, missed opportunities, and costly mistakes. Additionally, issues have different implications over time and spatial scales, and when considered in local contexts, are more nuanced and complex. Recent events also emphasize the critical need to consider social and environmental justice and to engage a range of interests in decision‐making processes. As policy makers, resource managers, and researchers, we must ask ourselves the tough questions that will lead to innovation and creative solutions. Questions about the potential unintended consequences and the political, social, economic, natural and/or ecological, hydrological, and technical feasibility of actually implementing solutions have largely gone unanswered. We call on our colleagues to work together on these challenges; to develop and use integrated tools like scenario planning and anticipatory decision frameworks; and collaborate on creating a "virtuous intersection." Join us in analyzing and implementing policy at the climate–land–energy–water interface. Abstract : Research Impact Statement : This commentary calls for dialogue to explore a 'virtuous' intersection of climate–land–energy and water systems to manage risk and build healthy, sustainable, and resilient communities.